Negotiating respect, Pentecostalism, masculinity, and the politics of spiritual authority in the Dominican Republic - Skoczen, Kathleen N. (Anthropos, 2017)
Keywords: dept.ant

Anthropological and ethnographic approach to breastfeeding. - Skoczen, Kathleen Nora (2012)
Dr. Skoczen continued research on bio-cultural and historical factors in breastfeeding, including ethnographic, in-depth interviews with new mothers, observing workshops, participation in conferences, and working on a manuscript devoted to this subject. She also worked on enhancing several of her classes and preparing a new course on cultural ecology.
Keywords: dept.ant; faculty_collection; sabbatical_report